2012 Frontiers in Education Conference Proceedings 2012
DOI: 10.1109/fie.2012.6462442
|View full text |Cite
|
Sign up to set email alerts
|

Understanding engineering transfer students: Demographic characteristics and educational outcomes

Abstract: Transfer students make up a significant share of engineering college graduates, yet their persistence is seldom studied, largely because of the lack of longitudinal data. This analysis used longitudinal data from 11 universities enrolling large numbers of engineering students to investigate the demographic characteristics and educational outcomes of transfer students in engineering relative to non-transfers. We find that students who transfer to four-year engineering programs are more likely to come from under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Assessment results indicate persistence of students in these programs to be on par with traditionally admitted engineering students, though factors exist that can impact persistence 26 . Page 26.203.3…”
Section: K-12 Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment results indicate persistence of students in these programs to be on par with traditionally admitted engineering students, though factors exist that can impact persistence 26 . Page 26.203.3…”
Section: K-12 Programsmentioning
confidence: 99%
“…Alternative Paths into Engineering: Some institutions conduct programs to address the needs of transfer students 26 , dual degree students 27 , pre-engineering majors 28 and other preparatory programs to build capacity in engineering [29][30][31] . Assessment results indicate persistence of students in these programs to be on par with traditionally admitted engineering students, though factors exist that can impact persistence 26 .…”
Section: K-12 Programsmentioning
confidence: 99%
“…Several studies have shown that two-year college students represent 42% of undergraduate enrollment and are historically over-represented in populations underrepresented in engineering (NSF, 2014;Ogilvie, 2014;Sullivan et al, 2012). In fact, recruiting and retaining 2-year college students has been discussed as an important avenue to help meet the challenge of increasing the number of STEM graduates.…”
Section: Introductionmentioning
confidence: 99%
“…Two-year college students represent an increasing proportion of all undergraduate enrollment growing from 43% in 2011 to 46% in 2013 and are historically over-represented populations underrepresented in engineering with over half of the Hispanic (57%), Native American (61%), and Black (52%) college students 4,6,7 . However, students starting in two-year colleges face many challenges, such as a lack of information about clear pathways, supportive policies, and systemic support between two-year and four-year institutions 8,9,10 .…”
Section: Introductionmentioning
confidence: 99%